Genotype-Phenotype Dissociation in Two Taiwanese Children with Molybdenum Cofactor Deficiency Caused by MOCS2 Mutation - Lee, Hsiu-Fen; Hsu, Chia-Chi; Chi, Ching-Shiang; Tsai, Chi-Ren (Neuropediatrics, 2021)
Background To describe the genotype-phenotype dissociation in two Taiwanese patients with molybdenum cofactor deficiency (MoCoD) caused by MOCS2 gene mutations.Patient Description Patient 1 exhibited early-onset neurological symptoms soon after birth, followed by subsequent myoclonic seizures and movement disorder. The brain magnetic resonance imaging (MRI) showed diffuse brain injury with cystic encephalomalacia along with bilateral globus pallidi involvement, hypoplasia of corpus callosum, and cerebellar atrophy. Patient 2 had a mild phenotype with prominent movement disorder after intercurrent illness, and the brain MRI showed selective injury of the bilateral globus pallidi and the cerebellum. Both patients had markedly low levels of plasma uric acid and harbored the same MOCS2 homozygous c.16C > T mutation. Patient 1 showed chronic regression of developmental milestones and died of respiratory failure at the age of 8 years, whereas patient 2 demonstrated improvement in motor function.Conclusion Genotype-phenotype dissociation could be noted in patients with MoCoD due to MOCS2 mutation. Patients with neonatal seizures, developmental delay, movement disorder, and motor regression after an illness, as well as focal or bilateral involvement of the globus pallidi on the neuroimages, should undergo biochemical testing of plasma uric acid. A pronounced plasma uric acid level is a good indicator of MoCoD. Early diagnosis can allow early provision of adequate genetic counseling.
Keywords: brain MRI; globus pallidus; hypouricemia; MOCS2 gene; molybdenum cofactor deficiency